2010
DOI: 10.2215/cjn.03550410
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Medical Evidence Form 2728 and Renal Biopsy for Glomerular Diseases

Abstract: Conclusions: Form 2728 does not accurately reflect the renal pathology diagnosis as captured by biopsy. The large degree of missing data and misclassification should be of concern to those performing epidemiologic research using Form 2728 information on glomerular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 21 publications
0
64
1
Order By: Relevance
“…First, we cannot confirm the validity of GN subtype designations obtained from the USRDS. A previous study measured agreement between biopsy-based diagnoses and USRDS-derived diagnoses among 227 patients with biopsy-proven GN (29). Poor overall agreement was largely explained by missing (57%) and GN not histologically examined (9%) diagnoses submitted to the USRDS; positive predictive values exceeded 90% once a specific GN subtype was selected.…”
Section: Discussionmentioning
confidence: 99%
“…First, we cannot confirm the validity of GN subtype designations obtained from the USRDS. A previous study measured agreement between biopsy-based diagnoses and USRDS-derived diagnoses among 227 patients with biopsy-proven GN (29). Poor overall agreement was largely explained by missing (57%) and GN not histologically examined (9%) diagnoses submitted to the USRDS; positive predictive values exceeded 90% once a specific GN subtype was selected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of community-level surrogates for socioeconomic status could introduce information bias. The source of data on medical comorbid conditions was the medical evidence report, which can have inconsistencies and errors, especially when completed by nonphysicians (30). Although every effort was made to reduce the effect of confounding, unmeasured confounders may limit the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary hypertension is a common consequence of longstanding kidney disease. Layton et al (2) further reported that causes of kidney failure were missing in up to 57% of patients.…”
Section: Limitations Of Esrd Classification On the Current Cms 2728 Formmentioning
confidence: 99%
“…Kidney biopsies are typically not performed in patients with longstanding diabetes or individuals without diabetes who lack heavy proteinuria. Surprisingly, even when kidney biopsies are performed, incorrect diagnoses may still be listed (2). This may relate to physicians' lack of awareness that biopsy data exist or that nonmedical personnel completed the form.…”
Section: Limitations Of Esrd Classification On the Current Cms 2728 Formmentioning
confidence: 99%
See 1 more Smart Citation